2021
DOI: 10.2196/31294
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes to Digital Health Research Repositories: Cross-sectional International Survey

Abstract: Background Digital health research repositories propose sharing longitudinal streams of health records and personal sensing data between multiple projects and researchers. Motivated by the prospect of personalizing patient care (precision medicine), these initiatives demand broad public acceptance and large numbers of data contributors, both of which are challenging. Objective This study investigates public attitudes toward possibly contributing to digi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 82 publications
(125 reference statements)
0
19
0
Order By: Relevance
“…Some empirical studies after that date retrieved by our search posed similar questions and reached conclusions similar to those of older studies. These conclusions included the same themes seen in the reviews, i.e., trust (including conditional trust and transparency), privacy, active engagement of participants, dynamic processes (featuring the possibility of choices over time), education and the raising of awareness regarding the benefits of research (Antommaria et al, 2018;Ballard et al, 2020;Barazzetti et al, 2020;Barnes et al, 2020;Carson et al, 2019;Meka et al, 2021;Nunes Vilaza et al, 2021), not to mention the lack of differences in attitudes between people with mental disorders and those without (Sundby et al, 2018). Remarkably, one study found differences between a pre-pandemic cohort and a pandemic cohort regarding data-sharing willingness, showing that dynamic processes would positively influence engagement and trust (Tosoni et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Some empirical studies after that date retrieved by our search posed similar questions and reached conclusions similar to those of older studies. These conclusions included the same themes seen in the reviews, i.e., trust (including conditional trust and transparency), privacy, active engagement of participants, dynamic processes (featuring the possibility of choices over time), education and the raising of awareness regarding the benefits of research (Antommaria et al, 2018;Ballard et al, 2020;Barazzetti et al, 2020;Barnes et al, 2020;Carson et al, 2019;Meka et al, 2021;Nunes Vilaza et al, 2021), not to mention the lack of differences in attitudes between people with mental disorders and those without (Sundby et al, 2018). Remarkably, one study found differences between a pre-pandemic cohort and a pandemic cohort regarding data-sharing willingness, showing that dynamic processes would positively influence engagement and trust (Tosoni et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Risks and benefits of data sharing must, therefore, be carefully weighed [10,23,49], and it is unclear whether specific datasets can be ethically released [10]. There is also concern about subsequent unethical and inappropriate projects in secondary use with a risk to privacy [30,36,50]. Ethical issues are mainly seen in further health data exchange [46].…”
Section: Ethical and Social Implicationsmentioning
confidence: 99%
“…Even when personal data are collected and used with good intentions, there can be no guarantees for their future use [29]. Possible data breaches, unauthorized data access, malicious attacks, or illegal data sales raise further cybersecurity concerns [29,33,50,59]. Healthcare facilities, in particular, are increasingly identified as attractive targets for hackers [49].…”
Section: Data Misusementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, digital health and health-data management have become a priority, firmly embedded in EU policy and funding goals (18). However, even if PHI represents an inalienable resource, personal preference in disclosing such information may limit access to PHI (8,(19)(20)(21)(22)(23)(24)(25). During the coronavirus disease 2019 (COVID-19) pandemic, the usefulness of sharing PHI was observed: PHI has been fundamental for contact tracing, managing the vaccination campaign, and other public health interventions (26,27).…”
Section: Introductionmentioning
confidence: 99%